A Comparative Evaluation of Nutritional Composition of Deep Sea and Coastal Shrimp off South-west Coast of India - Jose Fernandez, T.; Anandan, R.; Zynudheen, A. A. (Fishery Technology, 2018)
The chemical composition of deep-sea shrimp Aristeus alcocki, Heterocarpus gibbosus, Plesionika spinipus and Metapenaeopsis andamanensis harvested by deep-sea shrimp trawlers operating off the south west coast of India were evaluated and the nutritional composition was compared with coastal shrimp Fenneropenaeus indicus and Penaeus monodon. Among deep sea shrimp, the highest protein content of 22.82% was observed in H. gibbosus, whereas protein content in other species were in the range of 18.81 – 22.33%. Protein content in P. monodon and F. indicus were estimated as 17.46 and 19.23% respectively. Higher protein content in the muscle of deep sea shrimp indicates that deep sea shrimp meat can be a good source of amino acids. Among the species studied, fat content was comparatively high in A. alcocki (3.18%) followed by H. gibbosus (2.72%). Deep sea shrimp were found to have higher mineral content and have a higher amount of calcium and sodium when compared to coastal shrimp. The essential and non-essential amino acids were found higher in A. alcocki (17.78 and 15.71 g 100 g respectively) than other deep sea and coastal shrimp.